Clinical characteristics of pediatric intussusception and predictors of bowel resection in affected patients - Wu, Ting-Hsuan; Huang, Go-Shine; Wu, Chang-Teng; Lai, Jin-Yao; Chen, Chien-Chang; Hu, Mei-Hua (Frontiers in Surgery, 2022)
Background: Surgery is required for the treatment of intussusception when enema reduction is unsuccessful, or when the patient develops peritonitis, bowel perforation, or intestinal damage. We aimed to evaluate the clinical and laboratory parameters that may be used to predict the need for bowel resection in children with intussusception. Methods: This observational retrospective study included children who were admitted to the pediatric emergency room with intussusception. Univariate and multivariate logistic regression models were used to evaluate factors associated with bowel resection. Results: In total, 584 children with intussusception were admitted to the pediatric emergency room; 129 of these children underwent surgery. Multivariate analysis revealed the following independent predictors of bowel resection for intussusception: symptoms for at least 2 days before surgery (OR = 6.863; p = 0.009), long intussusception (OR = 5.088; p = 0.014), pathological lead point (OR = 6.926; p = 0.003), and intensive care unit admission (OR = 11.777; p = 0.001) were factors independently associated with bowel resection. Conclusion: Symptoms for at least 2 days before surgery, long intussusception, pathological lead, and intensive care unit admission were predictors of bowel resection in children with intussusception. These findings can be used to identify patients at high risk of needing surgery and bowel resection.